THE EFFECT OF VOCABULARY MASTERY AND LEARNING MOTIVATION ON STUDENTS WRITING SKILLS IN NARRATIVE TEXTS - Mega Asriany Dewi (Universitas Indraprasta PGRI, 2021)
Abstract: This research aims to know the Effects of vocabulary and Learning Motivation on students’ writing skills in Narrative text. The population is 150 students. The sample is 84 students. The method is the survey method. Data collecting is taken through a test that consists of a multiplechoice test, questioner, and writing test. The research shows that: 1) there are significant effects of vocabulary mastery and Learning Motivation on students’ writing skills in narrative text. That is proved by Sig value 0,000 < 0,05 and Fo = 10,640; 2) there is a significant effect of vocabulary mastery towards students’ writing skills in narrative text. That is proved by Sig value 0,004 < 0,05 and to = 2,930. 3). There is a significant effect of Learning Motivation on students’ writing skills innarrative text. That is proved by Sig value 0,009< 0,05 and to = 2,678.Keywords: vocabulary mastery; learning motivation; writing skill; narrative text.